2020
DOI: 10.3390/brainsci10090648
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Poststroke Motor-Function Recovery with Repetitive Transcranial Magnetic Stimulation by Regulating the Interhemispheric Imbalance

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive brain-stimulation technique that transiently modulates cerebral cortex excitability, achieving overall positive results in poststroke motor-function recovery. Excessive inhibition of the ipsilesional-affected hemisphere by the contralesional-unaffected hemisphere has seriously hindered poststroke motor-function recovery. Hence, intracortical disinhibition can be used as an approach to managing poststroke brain injury. This technique promotes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Excitatory rTMS includes high-frequency rTMS (HF-rTMS) or intermittent theta-burst stimulation (iTBS), which can increase cortical excitability, whereas inhibitory rTMS includes low-frequency rTMS (LF-rTMS) or continuous theta-burst stimulation (cTBS), which can suppress cortical excitability ( 18 , 19 ). According to the interhemispheric inhibition (IHI) model, a theoretical model commonly used to guide the use of rTMS in motor rehabilitation after stroke, there is abnormally increased transcallosal inhibition from the contralateral to ipsilateral hemisphere after stroke, resulting in decreased cortex excitability of the ipsilateral hemisphere and increased cortex excitability of the contralateral hemisphere ( 20 , 21 ). Therefore, excitatory rTMS is usually applied to the ipsilesional hemisphere, while inhibitory rTMS is applied to the contralateral hemisphere ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Excitatory rTMS includes high-frequency rTMS (HF-rTMS) or intermittent theta-burst stimulation (iTBS), which can increase cortical excitability, whereas inhibitory rTMS includes low-frequency rTMS (LF-rTMS) or continuous theta-burst stimulation (cTBS), which can suppress cortical excitability ( 18 , 19 ). According to the interhemispheric inhibition (IHI) model, a theoretical model commonly used to guide the use of rTMS in motor rehabilitation after stroke, there is abnormally increased transcallosal inhibition from the contralateral to ipsilateral hemisphere after stroke, resulting in decreased cortex excitability of the ipsilateral hemisphere and increased cortex excitability of the contralateral hemisphere ( 20 , 21 ). Therefore, excitatory rTMS is usually applied to the ipsilesional hemisphere, while inhibitory rTMS is applied to the contralateral hemisphere ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we examined if the combination of 1 Hz TMS is able to affect the upper extremity in patients with postischemic stroke [33]. It is suggested that intensive motor training combined with TMS is able to improve the WMFT log performance time from 3.23 (1.70-4.07) to 2.51 (1.36-3.86) and the total score of UEFMA from 48 to 51 (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) in patients with mild to moderate stroke [13]. The motor function showed significant differences between TMS with the rehabilitation program and TMS on the 7th day of upper extremity postischemic stroke (Table 3).…”
Section: Results and Dissectionmentioning
confidence: 99%
“…The increasing dysfunction may affect ADL and patient's quality of life [12]. Many studies show that intensive motor training with low-frequency TMS is able to increase motor function and daily activity on the upper extremity in patients with post-ischemic stroke [13].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing results between studies and inferring mechanisms is particularly challenging due to the lack of consistency in stimulation parameters and high injury variability (Fisicaro et al, 2019;Yuan et al, 2020). Additional studies are needed to adequately compare the effects of a wider range of stimulation parameters to determine parameter regimes that promote optimal recovery according to individual characteristics.…”
Section: Non-invasive Brain Stimulationmentioning
confidence: 99%